Composite battery diaphragm, preparation method thereof, secondary battery cell and battery pack
By using electrospinning technology to prepare the liquid-retaining safety fiber layer on the polymer film of the battery cell, the problem of electrolyte drying is solved, the liquid-retaining and safety of the battery is improved, and a longer cycle life and higher energy density is achieved.
Patent Information
- Application Number
- CN202411847146.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-28
AI Technical Summary
During the charging and discharging cycle, the electrolyte drys out due to the expansion and contraction of the negative electrode material during the charge and discharge cycle, which in turn affects the energy density and cycle stability of the battery.
Electrospinning technology is used to prepare a liquid-retaining safety fiber layer on the polymer film to form a composite battery separator to improve the liquid-retaining and safety of the battery.
It significantly improves the liquid retention and safety of the battery separator, extends the battery cycle life, increases the energy density, and reduces safety hazards.
Smart Images

Figure CN119725979A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of secondary batteries, and in particular to a composite battery separator, a preparation method thereof, a secondary battery cell and a battery pack. Background Art
[0002] Lithium-ion batteries, lithium metal batteries, sodium-ion batteries and sodium metal batteries have advantages such as high energy density and long cycle life, and have gradually become the mainstream development direction in the era of electrification. Among them, the negative electrode materials of lithium-ion batteries generally use materials such as graphite or silicon-based materials, which have a large volume expansion during the charge and discharge cycle; the negative electrode materials of sodium-ion batteries generally use materials such as hard carbon, and there are generally two processes of "adsorption" and "hole filling" during the charging process; the negative electrode materials of lithium metal batteries and sodium metal batteries use metallic lithium and metallic sodium respectively.
[0003] At present, the main failure modes of lithium (ion / metal) batteries or sodium (ion / metal) batteries are: failure of active material structure, loss of active lithium, increase in internal resistance of battery cells, and depletion of electrolyte. According to a large number of existing literature, the direct cause of battery cell failure is mainly due to depletion of electrolyte. The main reasons are: the continuous expansion and contraction of graphite and silicon-based negative electrodes of lithium-ion batteries during the charge and discharge cycle causes the continuous rupture and generation of SEI, which in turn consumes a large amount of limited electrolyte inside the battery cell; the active lithium / sodium metal formed by the hard carbon negative electrode of lithium / sodium ion batteries during the charge and discharge cycle causes the continuous rupture and generation of SEI on its surface due to the high activity of the surface, which in turn consumes a large amount of limited electrolyte inside the battery cell; metal batteries and sodium metal batteries form a lithium metal film or sodium metal film with high specific surface area and high activity on the negative electrode, which causes the continuous rupture and generation of SEI on its surface, which in turn consumes a large amount of limited electrolyte inside the battery cell.
[0004] In addition, it has been verified that after the failed lithium (ion / metal) battery or sodium (ion / metal) battery is supplemented with electrolyte for two or more times, the battery cell still has high electrochemical performance; at the same time, it has been verified that the current single-layer lithium metal battery can be cycled for more than 500 cycles due to its high liquid retention, but the multi-layer lithium metal battery has significantly reduced cycle performance due to insufficient liquid retention. Regarding this point, patent CN112993463A increases the liquid retention of the battery cell by placing porous foam on the surface of the bare core to improve the long-term cycle performance of the battery cell. However, in actual use, only the position where the outer surface of the single core contacts the porous foam has sufficient liquid retention, and there is still insufficient electrolyte inside the battery core.
[0005] At the same time, in the current development process of battery cells, most battery manufacturers use extreme design and extreme manufacturing methods to improve the energy density and rate performance of battery cells to ensure user experience. However, in the subsequent long-term use process, the performance of the battery cells will obviously decay, and there will even be major safety hazards, which will seriously affect the user experience. After disassembling and analyzing many failed battery cells, it was found that most of the failure modes of the current battery cells are electrolyte drying up. Therefore, increasing the liquid retention of the battery cell can significantly improve the long-term cycle performance and rate performance of the battery cell.
[0006] However, in the actual battery cell design process, the methods of increasing the liquid retention of the battery cell often significantly reduce the energy density of the battery cell and the operability of the actual preparation process. At the same time, when the battery cell retains a large amount of liquid, it is easy to have uneven stress release between the pole pieces, resulting in poor uniformity of the pole piece interface.
[0007] Based on this, how to specifically design the internal components of a secondary battery cell so that the cell can have both high electrolyte retention and high energy density is one of the important technical issues that need to be solved in this field. Summary of the invention
[0008] The main purpose of the present invention is to provide a composite battery separator, a preparation method thereof, a secondary battery cell and a battery pack to solve the problem in the prior art that it is difficult to achieve both high energy density and high cycle stability due to the low liquid retention of the battery cell.
[0009] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a method for preparing a composite battery separator, comprising: step S1, providing a polymer film; step S2, preparing a liquid-retaining safety fiber: step S2-1, mixing a silicon source, water and a pH adjuster to obtain a first slurry; step S2-2, preparing a template as a second slurry; step S2-3, mixing the first slurry with the second slurry and then electrospinning to obtain a precursor fiber; step S2-4, the precursor fiber is successively dried, pre-oxidized and calcined to obtain a liquid-retaining safety fiber; step S3, after pulping the liquid-retaining safety fiber, it is coated on one side surface of the polymer film, and after drying, a liquid-retaining safety layer is formed on the surface of the polymer film, thereby obtaining a composite battery separator.
[0010] Further, in step S2-1, the weight ratio of the silicon source, water and pH adjuster is (0.8-1.0):1:(0.11-0.12); and / or the silicon source is tetraethyl orthosilicate; and / or the pH adjuster is selected from one or more of phosphoric acid, phosphorous acid and citric acid; and / or the pH value of the first slurry is 4-7, preferably 5.5-6.0.
[0011] Furthermore, in step S2-2, the mass concentration of the template in the second slurry is 10wt% to 12wt%; and / or the template is selected from one or more of polyvinyl alcohol, polyacrylonitrile, polyethylene oxide and polystyrene.
[0012] Furthermore, in step S2-3, the first slurry and the second slurry are mixed in a weight ratio of 1:(0.8-1.0).
[0013] Furthermore, in step S2-3, during the electrospinning process, the spinning distance is 0.5 cm to 30 cm, the spinning voltage is 5 kV / cm to 50 kV / cm, and the liquid pushing speed is 0.1 mm / min to 5.0 mm / min.
[0014] Further, in step S2-4, drying is performed at 60°C to 80°C; and / or, pre-oxidation is performed at 200°C to 300°C; and / or, calcination is performed at 800°C to 1000°C.
[0015] Furthermore, the thickness of the liquid-retaining safety layer is 3 μm to 5 μm.
[0016] The second aspect of the present invention provides a composite battery separator, which is prepared by the preparation method of the above-mentioned composite battery separator, and the composite battery separator includes a polymer film and a liquid-retaining safety layer arranged on the surface of one side of the polymer film, and the thickness of the polymer film is 3μm to 25μm, preferably 12μm to 15μm; the polymer film is selected from PE film, PP film, PE / PP composite film, PE / Al2O3 coating film, PE / AlOOH coating film, PP / Al2O3 coating film, PP / AlOOH coating film, PE / PVDF coating film, PP / PVDF coating film, PE / Al2O3 / PVDF composite coating film, PP / Al2O3 / PVDF composite coating film, PI film, aramid film, PE / aramid coating film, PE / Al2O3 / aramid composite coating film One or more, preferably PP film and / or PE film.
[0017] Furthermore, the bulk density of the liquid-retaining safety layer is 2150 mg cm –3 ~2250mg·cm –3 , preferably 2180 mg·cm –3 ~2214mg·cm –3 The liquid-retaining safety layer has a porous structure, and the porosity of the liquid-retaining safety layer is 97.0% to 99.9%, preferably 97.44% to 99.85%.
[0018] The third aspect of the present invention provides a secondary battery cell, comprising a positive electrode sheet, a negative electrode sheet and a separator, the negative electrode sheet comprising a negative electrode collector and a negative electrode active layer arranged on at least one side surface of the negative electrode collector, the positive electrode sheet comprising a positive electrode collector and a positive electrode active layer arranged on at least one side surface of the positive electrode collector, the separator is arranged between the negative electrode active layer and the positive electrode active layer, the separator is the above-mentioned composite battery separator, and the liquid retaining safety layer in the composite battery separator is arranged in contact with the negative electrode active layer.
[0019] Furthermore, the liquid retention capacity of the secondary battery cell is 1.25 g / Ah to 2.85 g / Ah, and the secondary battery cell is selected from lithium ion battery cells, sodium ion battery cells, lithium metal battery cells, sodium metal battery cells, magnesium ion battery cells, and aluminum ion battery cells, preferably lithium ion battery cells.
[0020] A fourth aspect of the present invention provides a battery pack, which includes the above-mentioned secondary battery cell.
[0021] By applying the technical solution of the present invention, the liquid-retaining safety fiber layer prepared by electrospinning, drying, pre-oxidation and calcination processes using a silicon source, a pH regulator and a template agent is coated on a polymer film, thereby significantly improving the liquid-retaining property and safety of the battery separator. The prepared composite battery separator can effectively retain the electrolyte and prevent internal short circuits in the battery, while having good mechanical strength and thermal stability, thereby significantly improving the cycle performance and safety performance of the secondary battery, and providing strong support for the high performance and high safety of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0023] Figure 1 This is the SEM characterization result of the liquid-retaining safety layer on the composite battery separator obtained in Example 1. DETAILED DESCRIPTION
[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0025] As described in the background technology, the battery cells in the prior art have the problem of having difficulty in balancing high energy density and high cycle stability due to the low liquid retention. In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing a composite battery separator, comprising: step S1, providing a polymer film; step S2, preparing a liquid-retaining safety fiber: step S2-1, mixing a silicon source, water and a pH regulator to obtain a first slurry; step S2-2, preparing a template agent into a second slurry; step S2-3, mixing the first slurry with the second slurry and electrospinning to obtain a precursor fiber; step S2-4, the precursor fiber is sequentially dried, pre-oxidized and calcined to obtain a liquid-retaining safety fiber; step S3, after pulping the liquid-retaining safety fiber, it is coated on one side of the polymer film, and after drying, a liquid-retaining safety layer is formed on the surface of the polymer film, thereby obtaining a composite battery separator.
[0026] The present invention significantly improves the liquid retention and safety of the battery separator by coating a liquid-retaining safety fiber layer prepared by electrostatic spinning, drying, pre-oxidation and calcination processes with a silicon source, a pH regulator and a template on a polymer film.
[0027] Specifically, in the process of obtaining the first slurry, the pH regulator is used to make the obtained first slurry acidic, and under acidic conditions, the silicon source is hydrolyzed in water to obtain a silicon precursor containing -OH (i.e., silanol). After that, the first slurry containing the silicon precursor is mixed with the second slurry, that is, the solution containing the template, and the precursor fiber is prepared by electrostatic spinning. After that, the precursor fiber is dried, pre-oxidized and calcined to obtain a hollow SiO2 nanofiber, i.e., a liquid-retaining safety fiber. After that, the liquid-retaining safety fiber is pulped and coated to form a liquid-retaining safety layer on one side of the polymer film, thereby obtaining a composite battery separator. The obtained composite battery separator can effectively retain the electrolyte and prevent internal short circuits in the battery, and at the same time has good mechanical strength and thermal stability, thereby significantly improving the cycle performance and safety performance of the secondary battery, and providing strong support for the high performance and high safety of the secondary battery.
[0028] In actual applications, step S3 also includes: using water as a dispersion liquid, preparing the liquid-retaining safety fiber into a slurry with a solid content of 0.05wt% to 0.10wt%, and then coating the resulting slurry on one side of the polymer film, and obtaining a liquid-retaining safety layer after drying, thereby obtaining a composite battery separator.
[0029] Furthermore, in step S2-1, the weight ratio of silicon source, water and pH regulator is (0.8-1.0): 1: (0.11-0.12). The precise control of this weight ratio promotes the uniform formation of silicon dioxide precursor, thereby improving the porosity and electrolyte retention capacity of the liquid-retaining safety fiber, and finally obtaining a liquid-retaining safety layer with high liquid-retaining effect and high mechanical properties, thereby improving the liquid-retaining property of the obtained composite diaphragm. In several typical embodiments, the silicon source is preferably ethyl orthosilicate; the pH regulator is selected from one or more of phosphoric acid, phosphorous acid and citric acid; and / or the pH value of the first slurry is 4-7, more preferably 5.5-6.5. The selection of the types of the above-mentioned silicon source and pH regulator can promote the increase of the hydrolysis rate of the silicon source in water, while at the same time well controlling the reaction process, so that the mixed spinning solution is stable and controllable in the subsequent spinning process, and optimizes the structure and performance of the resulting precursor fiber and liquid-retaining safety fiber, thereby improving the liquid-retaining capacity of the composite battery separator in which the prepared liquid-retaining safety layer is located.
[0030] When preparing the second slurry, the template is used to form the fiber morphology, and further preferably its mass concentration is 10wt% to 12wt%, which can promote the stable formation of the precursor fiber during the electrospinning process, while maintaining its porous structure, thereby obtaining a liquid-retaining safety layer with better liquid-retaining properties and mechanical properties, and improving the various performances of the battery in which it is located. In order to further optimize the morphology and porosity of the obtained precursor fiber and the liquid-retaining safety fiber, the template is preferably selected from one or more of polyvinyl alcohol, polyacrylonitrile, polyethylene oxide and polystyrene.
[0031] Furthermore, in step S2-3, the first slurry and the second slurry are mixed in a weight ratio of 1: (0.8-1.0). The control of the above ratio can improve the structural stability and performance consistency of the precursor fiber obtained by electrospinning in the subsequent processing process, thereby obtaining a liquid-retaining safety fiber with better performance, and then the liquid-retaining safety layer with better liquid-retaining function is formed by pulping and coating, thereby improving the cycle stability of the battery in which it is located.
[0032] In several typical implementations, in step S2-3, during the electrospinning process, the spinning distance is 0.5 cm to 30 cm, the spinning voltage is 5 kV / cm to 50 kV / cm, and the liquid pushing speed is 0.1 mm / min to 5.0 mm / min. The optimization of the above electrospinning parameters can make the formed precursor fiber have a better and more uniform porous structure, so as to form more stable SiO2 nanofibers in the subsequent process.
[0033] In several more typical embodiments, in order to obtain a liquid-retaining safety layer with better liquid-retaining properties and mechanical properties, in step S2-3, during the electrospinning process, the spinning distance is 15 cm to 20 cm, the spinning voltage is 10 kV / cm to 20 kV / cm, and the liquid pushing speed is 0.2 mm / min to 0.5 mm / min.
[0034] Furthermore, in order to more thoroughly remove the non-crystallized water on the surface and inside of the precursor fiber while keeping it morphologically stable, it is preferred that in step S2-4, drying is performed at 60°C to 80°C. The preferred pre-oxidation is performed at 200°C to 300°C because the selection of this temperature range can promote the further optimization of the surface properties and internal structure of the precursor fiber after dehydration, and improve its thermal stability and mechanical strength. At the same time, pre-oxidation within this temperature range is also conducive to the subsequent calcination process, thereby obtaining a liquid-retaining safety fiber with a better microporous structure. Calcination is performed at 800°C to 1000°C. The above-mentioned preferred calcination temperature can more thoroughly remove the residual organic components in the precursor fiber, form a stable silica fiber structure, and then significantly improve the thermal stability and electrolyte retention capacity of the composite battery separator after coating to form a liquid-retaining safety layer.
[0035] Also, as for the thickness of the liquid-retaining safety layer, it is preferably 3 μm to 5 μm, so as to improve the liquid-retaining performance of the diaphragm while maintaining its good mechanical strength and low resistance characteristics, thereby allowing the battery system in which it is located to exhibit higher comprehensive performance.
[0036] The second aspect of the present invention provides a composite battery separator, which is prepared by the preparation method of the above-mentioned composite battery separator, and the composite battery separator includes a polymer film and a liquid-retaining safety layer arranged on the surface of one side of the polymer film, and the thickness of the polymer film is 3μm to 25μm, preferably 12μm to 15μm; the polymer film is selected from PE (polyethylene) film, PP (polypropylene) film, PE / PP composite film, PE / Al2O3 coating film, PE / AlOOH coating film, PP / Al2O3 coating film, PP / AlOOH coating film, PE / PVDF (polyvinylidene fluoride) coating film, PP / PVDF coating film, PE / Al2O3 / PVDF composite coating film, PP / Al2O3 / PVDF composite coating film, PI (polyimide) film, aramid film, PE / aramid coating film, PE / Al2O3 / aramid composite coating film, one or more of PP film and / or PE film, preferably PP film and / or PE film.
[0037] The above thickness and material selection of the polymer film can make the composite battery separator have good mechanical strength and porosity. However, as mentioned in the background technology, the porosity of the polymer film in the separator is relatively large and the pore size is also relatively large. When the electrolyte flows between the electrodes, the electrolyte is easily sucked out from the micropores, resulting in the loss of electrolyte on the surface of the negative electrode active layer, that is, there is a problem of poor liquid retention. The present invention, by providing a liquid-retaining safety layer with a high elastic liquid-retaining effect thereon, coordinates the intrinsic pore characteristics of the polymer membrane well, which not only improves the isolation effect of the separator on the electrolyte, but also increases the liquid retention of the battery cell, that is, improves the liquid retention and safety of the battery, and also allows the battery to exhibit high energy density and long cycle life.
[0038] Furthermore, the bulk density of the liquid-retaining safety layer is preferably 2150 mg·cm –3 ~2250mg·cm –3 , preferably 2180 mg·cm –3 ~2214mg·cm –3 , so that while improving the liquid retention performance of the liquid retention safety layer, it can maintain its good mechanical strength and electrolyte permeability. In addition, the liquid retention safety layer is a porous structure, and the pore size of the liquid retention safety layer is 170nm~360nm, and the porosity is 97.0%~99.9%, preferably 97.44%~99.85%. The above control of the porosity of the liquid retention safety layer can maintain good ion conductivity while improving its ability to retain electrolyte. Especially with regard to the optimization of its pore size, because the microstructure of the polymer membrane also contains a large number of holes, the pore size of the liquid retention safety layer on it is preferably as above based on the porous structure of the entire diaphragm, which is more conducive to improving the overall structural consistency and mechanical strength uniformity of the resulting composite battery diaphragm, and ultimately enables the battery in which it is located to have high comprehensive performance.
[0039] The third aspect of the present invention provides a secondary battery cell, including a positive electrode sheet, a negative electrode sheet and a separator, the negative electrode sheet includes a negative current collector and a negative active layer arranged on at least one side of the surface of the negative current collector, the positive electrode sheet includes a positive current collector and a positive active layer arranged on at least one side of the surface of the positive current collector, the separator is arranged between the negative active layer and the positive active layer, the separator is the above-mentioned composite battery separator, and the liquid-retaining safety layer in the composite battery separator is arranged in contact with the negative active layer. The introduction of the above-mentioned composite separator with high liquid retention not only improves the liquid retention and safety of the battery cell, but also optimizes the internal structure of the battery, improves the cycle performance and energy density of the battery, and is suitable for secondary battery cells that require high energy density, long cycle life and good safety.
[0040] In particular, in order to coordinate the mechanical properties of each structure so that the resulting battery exhibits higher cycle stability, the thickness ratio of the negative electrode active layer to the liquid-retaining safety layer is preferably (12 to 26):1.
[0041] Furthermore, the liquid retention of the secondary battery cell is 1.25 g / Ah to 2.85 g / Ah. The high liquid retention within this range can more effectively improve the liquid retention and safety of the battery cell, thereby making it have a longer cycle life.
[0042] In several preferred embodiments, the secondary battery cell is selected from lithium ion battery cells, sodium ion battery cells, lithium metal battery cells, sodium metal battery cells, magnesium ion battery cells, aluminum ion battery cells, and more preferably lithium ion battery cells.
[0043] In several more preferred embodiments, the negative electrode active layer is selected from a metal lithium layer or a graphite layer. More preferably, the negative electrode active layer is a graphite layer, and the compaction density of the graphite layer is 1.5 g / cm 3 ~1.6g / cm 3 , surface density is 100g / m 2 ~120g / m 2 The porosity is 28% to 30%, so as to better match the various properties of the above-mentioned composite battery separator, especially the microstructural characteristics, so that the battery in which the two are located can show higher energy density and longer cycle life.
[0044] The fourth aspect of the present invention provides a battery pack, which includes the above-mentioned secondary battery cell. Since the obtained battery cell has good electrical properties, especially high cycle stability, the corresponding battery pack also exhibits better electrical properties and has high application value.
[0045] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0046] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0047] Example 1
[0048] A method for preparing a lithium-ion battery cell:
[0049] 1. Preparation of composite battery separator:
[0050] (1) A PE film with a thickness of 12 μm is used as a polymer film;
[0051] (2-1) TEOS (tetraethyl orthosilicate), H2O, and H3PO4 were added to a reactor in a mass ratio of TEOS:H2O:H3PO4=1:1:0.11, and the mixture was sealed and stirred at room temperature for 8 hours to obtain a first slurry with a pH of 6;
[0052] (2-2) using polyvinyl alcohol (PVA) as a template, preparing a 10 wt % PVA aqueous solution, i.e., the second slurry;
[0053] (2-3) The first slurry and the second slurry are mixed in a mass ratio of 1:1, and then electrospinning is performed; the parameters of the electrospinning process are set as follows: spinning distance is 15 cm, spinning voltage is 12 kV / cm, and liquid pushing speed is 0.5 mm / min;
[0054] (2-4) The spun precursor fiber is first dried in an oven at 80°C, then placed in a furnace for pre-oxidation at 200°C, and then heated to 800°C for calcination to obtain a liquid-retaining safety fiber;
[0055] (3) Using water as the dispersion liquid and PVP as the dispersing aid (5‰), the obtained liquid-retaining safety fiber is prepared into a slurry with a solid content of 0.05wt%, and then the obtained slurry is coated on one side of the polymer film. After drying, a liquid-retaining safety layer with a thickness of 3μm is obtained, thereby obtaining a composite battery separator.
[0056] The surface of the composite battery separator coated with the liquid-retaining safety layer was characterized by SEM. Figure 1 .
[0057] 2. Preparation of lithium-ion battery cells:
[0058] Aluminum foil is used as the positive electrode current collector, and single crystal LiNi 0.6 Co 0.2 Mn 0.2 O2 is used as the positive electrode active material with a compaction density of 3.4 g / cm 3 , surface density is 190g / m 2 , N / P is set to 1.1, and a positive electrode sheet is prepared;
[0059] Copper foil was used as the negative electrode current collector and graphite was used as the negative electrode active material with a compaction density of 1.6 g / cm 3 , surface density is 120g / m 2 After rolling, a negative electrode sheet is obtained, and the porosity of the negative electrode active layer is 28% and the thickness is 75 μm;
[0060] The prepared electrode sheets and the composite battery separator are stacked in the order of positive electrode sheet - separator - negative electrode sheet, wherein the liquid retaining safety layer in the composite battery separator is in contact with the negative electrode active layer on the negative electrode sheet, and a 10Ah lithium-ion battery cell is prepared after stacking, packaging and liquid injection.
[0061] Among them, the thickness ratio of the negative electrode active layer on the negative electrode plate to the liquid retaining safety layer is 25:1.
[0062] Example 2
[0063] A method for preparing a lithium-ion battery cell:
[0064] 1. Preparation of composite battery separator:
[0065] (1) A PP film with a thickness of 15 μm is used as a polymer film;
[0066] (2-1) TEOS (tetraethyl orthosilicate), H2O, and H3PO4 were added to a reactor in a mass ratio of TEOS:H2O:H3PO4=0.8:1:0.12, and the mixture was sealed and stirred at room temperature for 8 hours to obtain a first slurry with a pH of 5.5;
[0067] (2-2) using polyvinyl alcohol (PVA) as a template, preparing a 12 wt % PVA aqueous solution, i.e., the second slurry;
[0068] (2-3) The first slurry and the second slurry are mixed at a mass ratio of 1:0.8, and then electrospinning is performed; the parameters of the electrospinning process are set as follows: spinning distance of 20 cm, spinning voltage of 20 kV / cm, and liquid pushing speed of 0.2 mm / min;
[0069] (2-4) The spun precursor fiber is first dried in an oven at 60°C, then placed in a furnace for pre-oxidation at 300°C, and then heated to 1000°C for calcination to obtain a liquid-retaining safety fiber;
[0070] (3) Using water as a dispersion liquid and HNBR (cyanide butyl rubber) as a dispersing aid (mass concentration of 5‰), the obtained liquid-retaining safety fiber is prepared into a slurry with a solid content of 0.1wt%, and then the obtained slurry is coated on one side of the polymer film. After drying, a liquid-retaining safety layer with a thickness of 3μm is obtained, thereby obtaining a composite battery separator.
[0071] 2. Preparation of lithium-ion battery cells:
[0072] A positive electrode sheet was prepared according to the conditions in Example 1;
[0073] Copper foil was used as the negative electrode current collector and graphite was used as the negative electrode active material with a compaction density of 1.55 g / cm 3, surface density is 120g / m 2 After rolling, a negative electrode sheet is obtained, and the porosity of the negative electrode active layer is 30% and the thickness is 77.5 μm;
[0074] A 10Ah lithium-ion battery cell was prepared according to the conditions in Example 1.
[0075] Among them, the thickness ratio of the negative electrode active layer to the liquid retaining safety layer on the negative electrode plate is 25.8:1.
[0076] Example 3
[0077] A method for preparing a lithium-ion battery cell:
[0078] 1. A composite battery separator having a liquid-retaining safety layer thickness of 5 μm was prepared according to the conditions in Example 1:
[0079] 2. Prepare a 10Ah lithium-ion battery cell according to the conditions in Example 1:
[0080] Among them, the thickness ratio of the negative electrode active layer on the negative electrode plate to the liquid retaining safety layer is 15:1.
[0081] Example 4
[0082] A method for preparing a lithium-ion battery cell:
[0083] 1. A composite battery separator having a liquid-retaining safety layer thickness of 3 μm was prepared according to the conditions in Example 1:
[0084] 2. Preparation of lithium-ion battery cells:
[0085] A positive electrode sheet was prepared according to the conditions in Example 1;
[0086] Copper foil was used as the negative electrode current collector and graphite was used as the negative electrode active material with a compaction density of 1.6 g / cm 3 , surface density is 100g / m 2 After rolling, a negative electrode sheet was obtained, and the porosity of the negative electrode active layer was 28% and the thickness was 62.5 μm;
[0087] A 10Ah lithium-ion battery cell was prepared according to the conditions in Example 1.
[0088] Among them, the thickness ratio of the negative electrode active layer to the liquid retaining safety layer on the negative electrode plate is 20.8:1.
[0089] Example 5
[0090] A method for preparing a lithium-ion battery cell:
[0091] 1. A composite battery separator having a liquid-retaining safety layer thickness of 3 μm was prepared according to the conditions in Example 1:
[0092] 2. Preparation of lithium-ion battery cells:
[0093] A positive electrode sheet was prepared according to the conditions in Example 1;
[0094] Copper foil was used as the negative electrode current collector and graphite was used as the negative electrode active material with a compaction density of 1.55 g / cm 3 , surface density is 100g / m 2 After rolling, a negative electrode sheet is obtained, and the porosity of the negative electrode active layer is 30% and the thickness is 64.5 μm;
[0095] A 10Ah lithium-ion battery cell was prepared according to the conditions in Example 1.
[0096] Among them, the thickness ratio of the negative electrode active layer to the liquid retaining safety layer on the negative electrode plate is 21.5:1.
[0097] Example 6
[0098] A method for preparing a lithium-ion battery cell:
[0099] 1. A composite battery separator having a liquid-retaining safety layer thickness of 5 μm was prepared according to the conditions in Example 1:
[0100] 2. Preparation of lithium-ion battery cells:
[0101] A positive electrode sheet was prepared according to the conditions in Example 1;
[0102] Copper foil was used as the negative electrode current collector and graphite was used as the negative electrode active material with a compaction density of 1.6 g / cm 3 , surface density is 100g / m 2 After rolling, a negative electrode sheet was obtained, and the porosity of the negative electrode active layer was 28% and the thickness was 62.5 μm;
[0103] A 10Ah lithium-ion battery cell was prepared according to the conditions in Example 1.
[0104] Among them, the thickness ratio of the negative electrode active layer on the negative electrode plate to the liquid retaining safety layer is 12.5:1.
[0105] Example 7
[0106] A method for preparing a lithium-ion battery cell:
[0107] The difference between this embodiment and embodiment 1 is that the preparation conditions of the positive electrode sheet are changed to:
[0108] Aluminum foil was used as the positive electrode current collector, single crystal LiFePO4 was used as the positive electrode active material, and the compaction density was 2.45 g / cm 3 , surface density is 213g / m 2 , N / P is set to 1.1, and the positive electrode sheet is prepared.
[0109] Example 8
[0110] A method for preparing a lithium-ion battery cell:
[0111] The only difference between this embodiment and embodiment 1 is that the negative electrode active layer on the negative electrode plate is changed to a metal lithium layer with a thickness of 100 μm.
[0112] At this time, the thickness ratio of the negative electrode active layer and the liquid retaining safety layer on the negative electrode sheet was changed to 33.3:1.
[0113] Example 9
[0114] A method for preparing a lithium-ion battery cell:
[0115] The only difference between this embodiment and embodiment 1 is that the mass ratio of TEOS, H2O, and H3PO4 in step (2-1) is changed to 0.5:1:0.2.
[0116] Example 10
[0117] A method for preparing a lithium-ion battery cell:
[0118] The only difference between this embodiment and embodiment 1 is that the mass ratio of TEOS, H2O, and H3PO4 in step (2-1) is changed to 1.5:1:0.05.
[0119] Embodiment 11
[0120] A method for preparing a lithium-ion battery cell:
[0121] The only difference between this embodiment and embodiment 1 is that the mass concentration of the PVA aqueous solution in step (2-2) is changed to 5 wt %.
[0122] Example 12
[0123] A method for preparing a lithium-ion battery cell:
[0124] The only difference between this embodiment and embodiment 1 is that the mass concentration of the PVA aqueous solution in step (2-2) is changed to 20 wt %.
[0125] Example 13
[0126] A method for preparing a lithium-ion battery cell:
[0127] The only difference between this embodiment and embodiment 1 is that the mass ratio of the first slurry to the second slurry in step (2-3) is changed to 2:1.
[0128] Embodiment 14
[0129] A method for preparing a lithium-ion battery cell:
[0130] The only difference between this embodiment and embodiment 1 is that the mass ratio of the first slurry to the second slurry in step (2-3) is changed to 1:2.
[0131] Embodiment 15
[0132] A method for preparing a lithium-ion battery cell:
[0133] The only difference between this embodiment and embodiment 1 is that the parameter settings of the electrospinning process in step (2-3) are changed to: spinning distance is 0.5 cm, spinning voltage is 5 kV / cm, and liquid pushing speed is 5.0 mm / min.
[0134] Example 16
[0135] A method for preparing a lithium-ion battery cell:
[0136] The only difference between this embodiment and embodiment 1 is that the parameter settings of the electrospinning process in step (2-3) are changed to: spinning distance is 30 cm, spinning voltage is 50 kV / cm, and liquid pushing speed is 0.1 mm / min.
[0137] Embodiment 17
[0138] A method for preparing a lithium-ion battery cell:
[0139] The only difference between this embodiment and embodiment 1 is that the drying temperature in step (2-4) is changed to 40°C, the pre-oxidation temperature is changed to 100°C, and the calcination temperature is changed to 500°C.
[0140] Embodiment 18
[0141] A method for preparing a lithium-ion battery cell:
[0142] The only difference between this embodiment and embodiment 1 is that the drying temperature in step (2-4) is changed to 100°C, the pre-oxidation temperature is changed to 400°C, and the calcination temperature is changed to 1500°C.
[0143] Embodiment 19
[0144] A method for preparing a lithium-ion battery cell:
[0145] The difference between this embodiment and embodiment 1 is only in step 1, that is, preparing a composite battery separator with a liquid-retaining safety layer thickness of 1 μm according to the conditions in embodiment 1.
[0146] At this time, the thickness ratio of the negative electrode active layer on the negative electrode plate to the liquid retaining safety layer is 75:1.
[0147] Embodiment 20
[0148] A method for preparing a lithium-ion battery cell:
[0149] The difference between this embodiment and embodiment 1 is only in step 1, that is, preparing a composite battery separator with a liquid-retaining safety layer thickness of 8 μm according to the conditions in embodiment 1.
[0150] At this time, the thickness ratio of the negative electrode active layer to the liquid retaining safety layer on the negative electrode plate is 9.4:1.
[0151] Comparative Example 1
[0152] A method for preparing a lithium-ion battery cell:
[0153] The only difference between this comparative example and Example 1 is that no composite battery separator is prepared, but the polymer film therein is directly used as a battery cell separator.
[0154] Comparative Example 2
[0155] A method for preparing a lithium-ion battery cell:
[0156] The only difference between this comparative example and Example 2 is that no composite battery separator is prepared, but the polymer membrane therein is directly used as the battery cell separator.
[0157] Comparative Example 3
[0158] A method for preparing a lithium-ion battery cell:
[0159] The only difference between this comparative example and Example 7 is that no composite battery separator is prepared, but the polymer film therein is directly used as the battery cell separator.
[0160] Comparative Example 4
[0161] A method for preparing a lithium-ion battery cell:
[0162] The only difference between this comparative example and Example 8 is that no composite battery separator is prepared, but the polymer membrane therein is directly used as the battery cell separator.
[0163] Comparative Example 5
[0164] A method for preparing a lithium-ion battery cell:
[0165] The only difference between this comparative example and Example 1 is that no liquid-retaining safety fiber is prepared. Instead, a SiO2 fiber product with a diameter of 30 nm is directly coated on one surface of the polymer film in accordance with step (3) in Example 1 to obtain a composite battery separator.
[0166] In this comparative example, since the purchased existing SiO2 fibers are different from the highly flexible and layered liquid-retaining safety fibers prepared in Example 1 or 2, they are mostly hard, brittle and fragile, making them difficult to composite with the polymer film, resulting in sample preparation failure.
[0167] Comparative Example 6
[0168] A method for preparing a lithium-ion battery cell:
[0169] The only difference between this comparative example and Example 1 is that step (2-4) is not performed, and instead the precursor fibers obtained by electrospinning in step (2-3) are directly coated on one surface of the polymer membrane in the manner of step (3) in Example 1 to obtain a composite battery separator.
[0170] Test Method
[0171] Bulk density of liquid-retaining safety layer: Turn on the liquid specific gravity balance, select pure water as the medium, and maintain the water bath temperature at (23 ± 2) ° C. First, use an electronic analytical balance to weigh about 10g of liquid-retaining safety fiber, wind it into a fiber ball of about 5cm in length, and put it into the liquid specific gravity balance, accurately weigh its mass, and then immerse the fiber ball in pure water to make it completely immersed in pure water, and constantly clamp the fiber ball with tweezers to exhaust all air. After the balance is stable, read the bulk density of the liquid-retaining safety fiber.
[0172] Internal pore size of liquid-retaining safety layer: The method of mercury intrusion is adopted, specifically: ① Sample preparation: Take 100g of liquid-retaining safety fiber, crush and screen it, place it in an oven, and dry it at a constant temperature of 110±5℃, then cool it to room temperature for use. ② Low-pressure analysis: Load the weighed sample into the dilatometer, seal it and weigh it. Put the dilatometer with the loaded sample into the low-pressure analysis chamber and start the low-pressure analysis. After the low-pressure analysis starts, the dilatometer is evacuated to 7Pa (50μm Hg), and then mercury injection begins. Vacuuming has two functions: one is to remove the impurity gas adsorbed by the sample in the dilatometer, and the other is to extract mercury from the mercury trap through negative pressure and make it enter the dilatometer for filling. The macropores in the material are filled during the low-pressure analysis process. ③ High-pressure analysis: After the low-pressure analysis is completed, take out the dilatometer, observe whether the mercury fills the dilatometer, weigh the mass of the dilatometer again (dilatometer + sample + mercury), and then put the dilatometer into the high-pressure chamber, remove the air in the high-pressure chamber, and tighten the high-pressure chamber. Select the high pressure analysis sample file, input the mass of the dilatometer, and start the high pressure analysis, with the maximum pressure reaching 207MPa (30000Psia). The small pores in the material are filled during the high pressure analysis. ④Data processing: During the test, the system records the pressure applied by the mercury injection and the amount of mercury injected in real time, and the average pore size, specific surface area and distribution of different pore size ranges of the sample can be calculated.
[0173] Porosity of the liquid-retaining safety layer: Porosity test method: Tested in accordance with standard T / CAAMTB 201-2024.
[0174] The amount of liquid retained inside the battery cell sample: weigh the battery cell shell M1, bare core M2, and electrolyte mass M3 respectively, calculate the total mass M4 of the battery cell after formation, exhaust and sealing, and the battery cell liquid retention m=M3-(M1+M2+M3-M4).
[0175] The first week coulombic efficiency of the battery sample: its calculation formula is: the first discharge capacity in the capacity division stage A3 / (the first charge capacity in the formation stage A1+the first charge capacity in the capacity division stage A2).
[0176] Capacity retention rate of battery cell samples: Under the conditions of 45°C and 1C / 1C, the capacity of the last cycle of battery cell capacity division is recorded as capacity A when the capacity retention rate is 100%. During subsequent use, the capacity decays, and the actual discharge capacity is A1, and the ratio A1 / A is recorded as the capacity retention rate.
[0177] The above test results are shown in Table 1.
[0178] Table 1
[0179]
[0180]
[0181] From the above description, it can be seen that the above embodiments of the present invention realize the provision of a liquid retaining safety layer with high elasticity, high porosity and high liquid retention capacity on the battery cell diaphragm, so that the resulting battery cell exhibits high energy density and cycle stability.
[0182] Specifically, by comparing the embodiments with comparative examples 1 to 4, it can be seen that the liquid-retaining safety layer prepared by the present invention can improve the performance of the composite battery separator in which it is located, and the energy density and cycle stability of the obtained battery cell are higher.
[0183] By comparing the embodiments with comparative example 5, it can be seen that the liquid-retaining safety fiber prepared by the preparation method provided by the present invention can more effectively form a liquid-retaining safety layer with excellent performance on the surface of the polymer film, thereby improving the electrical performance of the obtained battery cell.
[0184] By comparing the embodiments with comparative example 6, it can be seen that after drying, pre-oxidation and calcination, the hollow SiO2 nanofibers, i.e., liquid-retaining safety fibers, are obtained, and the liquid-retaining safety layer formed by the fibers can more significantly improve the performance of the battery cell.
[0185] By comparing Examples 1 to 7 with Example 8, it can be seen that when the thickness ratio of the negative electrode active layer to the liquid retaining safety layer is preferably (12-26):1, the battery containing the prepared composite battery separator can exhibit higher cycle stability.
[0186] By comparing Examples 1 to 7 with Examples 9 and 10, it can be seen that in the process of preparing the liquid-retaining safety fiber, when the weight ratio of the preferred silicon source, water and pH adjuster is (0.8-1.0):1:(0.11-0.12), the porosity and electrolyte retention capacity of the prepared liquid-retaining safety fiber can be improved, thereby improving the liquid retention of the composite diaphragm, and obtaining a battery cell with higher energy density and cycle stability.
[0187] By comparing Examples 1 to 7 with Examples 11 and 12, it can be seen that in the process of preparing the liquid-retaining safety fiber, when forming the second slurry, its mass concentration is preferably 10wt% to 12wt%, which can promote the stable formation of the precursor fiber during the electrospinning process, thereby obtaining a liquid-retaining safety layer with better liquid retention and mechanical properties, thereby improving the various performances of the battery in which it is located.
[0188] By comparing Examples 1 to 7 with Examples 13 and 14, it can be seen that in the process of preparing the liquid-retaining safety fiber, the first slurry and the second slurry are preferably mixed in a weight ratio of 1: (0.8 to 1.0), which can improve the structural stability and performance consistency of the precursor fiber obtained by electrospinning in the subsequent processing process, thereby obtaining liquid-retaining safety fibers with better performance, and more effectively improve the cycle stability of the battery in which it is located after coating and drying into layers.
[0189] By comparing Examples 1 to 7 with Examples 15 and 16, it can be seen that in the electrospinning process, the preferred spinning distance is 15 cm to 20 cm, the spinning voltage is 10 kV / cm to 20 kV / cm, and the liquid pushing speed is 0.2 mm / min to 0.5 mm / min, which can form more stable SiO2 nanofibers, thereby obtaining a composite battery separator with higher liquid retention and safety, and the electrical performance of the corresponding battery is also correspondingly higher.
[0190] By comparing Examples 1 to 7 with Examples 17 and 18, it can be seen that it is preferred that drying is carried out at 60°C to 80°C, pre-oxidation is carried out at 200°C to 300°C, and calcination is carried out at 800°C to 1000°C. The coordinated cooperation of the three-stage temperatures can form a stable silica fiber structure, and then after coating to form a liquid-retaining safety layer, the thermal stability and electrolyte retention capacity of the composite battery separator are significantly improved, and ultimately the battery cell in which it is located exhibits higher cycle stability.
[0191] By comparing Examples 1 to 7 with Examples 19 and 20, it can be seen that the preferred thickness of the liquid-retaining safety layer is 3 μm to 5 μm, which can improve the liquid-retaining performance of the diaphragm while maintaining its good mechanical strength and low resistance characteristics, thereby allowing the battery system in which it is located to exhibit higher comprehensive performance.
[0192] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0193] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite battery separator, characterized in that: include: Step S1, providing a polymer film; Step S2, preparing liquid-retaining safety fiber: Step S2-1, mixing a silicon source, water and a pH adjuster to obtain a first slurry; Step S2-2, preparing the template into a second slurry; Step S2-3, mixing the first slurry and the second slurry and performing electrostatic spinning to obtain precursor fibers; Step S2-4, the precursor fiber is dried, pre-oxidized and calcined in sequence to obtain the liquid-retaining safety fiber; Step S3, pulping the liquid-retaining safety fiber and coating it on one side surface of the polymer film, and after drying, forming a liquid-retaining safety layer on the surface of the polymer film, thereby obtaining the composite battery separator.
2. The method for preparing a composite battery separator according to claim 1, characterized in that: In step S2-1, the weight ratio of the silicon source, the water and the pH adjuster is (0.8-1.0):1:(0.11-0.12); and / or, The silicon source is tetraethyl orthosilicate; and / or, The pH regulator is selected from one or more of phosphoric acid, phosphorous acid and citric acid; and / or, The pH value of the first slurry is 4-7, preferably 5.5-6.
0.
3. The method for preparing a composite battery separator according to claim 1 or 2, characterized in that: In step S2-2, the mass concentration of the template in the second slurry is 10wt% to 12wt%; and / or, The template is selected from one or more of polyvinyl alcohol, polyacrylonitrile, polyethylene oxide and polystyrene.
4. The method for preparing a composite battery separator according to any one of claims 1 to 3, characterized in that: In step S2-3, the first slurry and the second slurry are mixed at a weight ratio of 1:(0.8-1.0).
5. The method for preparing a composite battery separator according to any one of claims 1 to 4, characterized in that: In step S2-3, during the electrospinning process, the spinning distance is 0.5 cm to 30 cm, the spinning voltage is 5 kV / cm to 50 kV / cm, and the liquid pushing speed is 0.1 mm / min to 5.0 mm / min.
6. The method for preparing a composite battery separator according to any one of claims 1 to 5, characterized in that: In step S2-4, The drying is carried out at 60°C to 80°C; and / or, The pre-oxidation is carried out at 200°C to 300°C; and / or, The calcination is carried out at 800°C to 1000°C.
7. The method for preparing a composite battery separator according to any one of claims 1 to 6, characterized in that: The thickness of the liquid-retaining safety layer is 3 μm to 5 μm.
8. A composite battery separator, characterized in that: The composite battery separator is prepared by the method for preparing a composite battery separator according to any one of claims 1 to 7, and the composite battery separator comprises a polymer film and the liquid-retaining safety layer disposed on one surface of the polymer film, and, The thickness of the polymer film is 3 μm to 25 μm, preferably 12 μm to 15 μm; The polymer film is selected from one or more of PE film, PP film, PE / PP composite film, PE / Al2O3 coating film, PE / AlOOH coating film, PP / Al2O3 coating film, PP / AlOOH coating film, PE / PVDF coating film, PP / PVDF coating film, PE / Al2O3 / PVDF composite coating film, PP / Al2O3 / PVDF composite coating film, PI film, aramid film, PE / aramid coating film, PE / Al2O3 / aramid composite coating film, preferably PP film and / or PE film.
9. The composite battery separator according to claim 8, characterized in that: The bulk density of the liquid-retaining safety layer is 2150 mg·cm –3 ~2250mg·cm –3 , preferably 2180 mg·cm –3 ~2214mg·cm –3 ; The liquid retaining safety layer is a porous structure, and the porosity of the liquid retaining safety layer is 97.0% to 99.9%, preferably 97.44% to 99.85%.
10. A secondary battery cell, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the negative electrode sheet comprises a negative current collector and a negative electrode active layer disposed on at least one side surface of the negative current collector, the positive electrode sheet comprises a positive current collector and a positive electrode active layer disposed on at least one side surface of the positive current collector, the separator is disposed between the negative electrode active layer and the positive electrode active layer, characterized in that: The separator is the composite battery separator according to claim 8 or 9, and the liquid-retaining safety layer in the composite battery separator is provided in contact with the negative electrode active layer.
11. The secondary battery cell according to claim 10, characterized in that: The liquid retention capacity of the secondary battery cell is 1.25 g / Ah to 2.85 g / Ah, and the secondary battery cell is selected from lithium ion battery cells, sodium ion battery cells, lithium metal battery cells, sodium metal battery cells, magnesium ion battery cells, and aluminum ion battery cells, preferably lithium ion battery cells.
12. A battery pack, characterized in that: The battery pack comprises the secondary battery cell according to claim 10 or 11.
Citation Information
Patent Citations
Battery cell with built-in buffer pad
CN112993463A